Ctenus monaghani spec. nov., a nocturnal hunter from the forest floor in Laos (Araneae: Ctenidae) - Jäger, Peter (Zootaxa, 2013)
The genus Ctenus Walckenaer 1805 was recently revised by Jäger (2012) for Laos and neighbouring countries. He followed the broader definition of the genus by Steyn et al. (1997) and recorded five species from Laos, three of which were described as new (Jäger 2012). In May 2012 one male of the genus Ctenus was collected in the Khammouan Province, Laos. It belongs to an undescribed species, which is described below.